A Doppler Compensation Method Based on the Sinusoidal Signal in OFDM Underwater Communication System - Do, Dinh Hung; Nguyen, Quoc Khuong (Old Journal, 2018)
In this paper, we propose a method uses to compensate Doppler frequency shift for underwater acoustic communication systems using OFDM technology. The calculation of the Doppler frequency shift compensation in the article is done in two steps. The first step is coarse synchronization through the use of the carrier signal attached to the end of each frame transmitted signal. In this step, based on the carrier signal to calculate the frequency deviation between the transmitter and receiver due to the relative motion between the transmitter and receiver causes Doppler effect. However, the calculation of the frequency shift is not exactly in coarse synchronization, then before decoding M-QAM, technical constellation phase rotation signal is applied to increase the quality of the received signal. The results of research and simulation, experimentation showed that the system can handle the underwater communication at speeds of more than 2m/s.